2018
DOI: 10.1007/s10120-018-0801-6
|View full text |Cite
|
Sign up to set email alerts
|

HOTAIR induces the ubiquitination of Runx3 by interacting with Mex3b and enhances the invasion of gastric cancer cells

Abstract: These results uncovered the novel interaction between HOTAIR and Runx3, and provided potential therapeutic targets on the metastasis of gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 24 publications
1
48
1
Order By: Relevance
“…Here, we described for the first time that the RNA-binding MEX3A affects GB proliferation, acting as an E3-ubiquitin ligase. So far, little is known about the role of this protein in carcinogenesis [21][22][23][24]26]. Although MEX3A is a member of the RNA-binding ubiquitin ligase MEX3 protein family, its function as E3-ligase and its potential substrates have not yet been described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we described for the first time that the RNA-binding MEX3A affects GB proliferation, acting as an E3-ubiquitin ligase. So far, little is known about the role of this protein in carcinogenesis [21][22][23][24]26]. Although MEX3A is a member of the RNA-binding ubiquitin ligase MEX3 protein family, its function as E3-ligase and its potential substrates have not yet been described.…”
Section: Discussionmentioning
confidence: 99%
“…MEX3 proteins play pivotal role in self-renewal and differentiation processes, with implications regarding stemness and carcinogenesis [20][21][22][23][24][25]. In particular, alterations of MEX3A activity have been described in gastric, colorectal and bladder cancers, although its mechanism of action and its potential substrates remain still elusive [21][22][23][24]26]. To date, only the RING finger domain of human MEX3C has been functionally and structurally characterized, and Retinoic acid-inducible gene I (RIG-I) is the unique substrate described for this E3 ligase [27].…”
mentioning
confidence: 99%
“…To understand the internal contact between lncRNA-miRNA-mRNA in the development and progression of GC, the present study constructed the ceRNA network by bioinformatics prediction based on differences in lncRNA, miRNA and mRNA expression from TCGA. Certain lncRNAs that exist in the network have been proven to interact with miRNA and mRNA and may be potential biomarkers in the diagnosis, therapy and prognosis of GC, including UCA1, HOTTIP, HOTAIR and H19 (45)(46)(47)(48). Additionally, a few genes from the ceRNA network, including CHRDL1, COL1A1, HOXC8 and ATAD2, have been reported to act as tumor oncogenes or suppressor genes, participating in tumor growth, invasion and metastasis (41,(49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…Runx3 endows gastric cells with the capacity of excessive proliferation and invasion (122). The combination of HOTAIR and Mex3b, a type of E3 ligase possessing RNA binding domains, can attenuate the degradation of Runx3, thus regulating cancer migration and invasion (123). Zeng et al (124) found that LINc00675 could enhance the phosphorylation of vimentin on Ser8 and the p53 signaling pathway.…”
Section: Long Non-coding Rnas (Lncrnas)mentioning
confidence: 99%
“…A novel therapeutic method for Gc relies on the elucidation of the mechanisms responsible for the development of Gc. Previous studies have screened out numerous circRNAs and lncRNAs with therapeutic potential (41)(42)(43)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)115,(118)(119)(120)(121)(123)(124)(125)(126)(127)(128)132,133,138,(140)(141)(142)(143)(144)(145), mainly by small interference in vitro and by inhibition of tumor burden in vivo. Various new signaling pathways were identified, which were connected with established cancer promoters or suppressors.…”
Section: Comparison Of Achievements Regarding Circrnas and Lncrnasmentioning
confidence: 99%